Pendampingan E-Commerce Bagi Pengrajin Tas - Nanik Susanti; Yudie Irawan; Wiwit Agus Triyanto (Muria Jurnal Layanan Masyarakat, 2019)
Craft bags in the village of Gulang has become a superior product of the village whose existence is able to lift the economy of the Gulang village community itself. There are at least 20 bag craftsmen in Gulang Village. One of them is Valya Bag’s bag craftsman who has been managed by Mr. Sutarno since 2008. So far, bag craftsmen in Gulang village including Valya Bag’s in producing bag crafts based on orders, entrepreneurs do not make products for stock. The product marketing system is also still manual, it still relies on communication media for direct interaction with consumers and is still centered on the location of certain places such as coming directly to the place of craftsman or when there is an exhibition. This kind of marketing model makes it difficult for potential buyers to access various information needs about the product, information about the latest prices due to limited promotional media. The bag craftsmen hope to expand the marketing area and add customers in order to increase the company's turnover and sustainable production. The purpose of community service is to help entrepreneurs in expanding marketing difficulties. Especially with e-marketing techniques as a means to optimize product marketing. In addition, this dedication team will provide training and assistance for managing e-marketing websites and make interesting product photos to support the website's appearance.